Pengaruh Social Media Marketing dan Experiential Marketing Terhadap Repurchase Intention di Indomaret Point Coffee Medan: Penelitian - Nayla Hanifah; Onan Marakali Siregar (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to determine the effect of social media marketing and experiential marketing on repurchase intention. The effect of social media marketing and experiential marketing will be analyzed partially and simultaneously on repurchase intention on consumers of Indomaret Point Coffee Medan. The form of research used is quantitative with an associative approach. The population in this study is unknown so that sampling is carried out using a non-probability sampling technique with a purposive sampling type. Primary data was obtained through direct distribution of questionnaires and secondary data was obtained through literature studies, previous research, and data obtained via the internet. The analysis methods used are validity test, reliability test, classical assumption test, multiple linear regression, partial test, simultaneous test, and determination test processed through SPSS software. The results of this study indicate that Social media marketing has a significant influence on Repurchase intention with t count> t table, namely 3.883> 1.984 with a significance of 0.000 <0.05. Experiential marketing has a significant influence on Repurchase intention with a t count of 4.863> 1.984 with a significance of 0.000 <0.05. In the simultaneous test, the Social Media Marketing and Experiential Marketing variables have a positive and significant effect on Repurchase Intention with a t-value of 169.551> 3.09 with a significance of 0.000 <0.05 and a coefficient of determination of 0.773, which indicates that the influence of the Social Media Marketing and Experiential Marketing variables can explain the Repurchase Intention variable by 77.3%, while the remaining 22.7% is influenced by other factors outside this study.